Peranan Modal Sosial dalam Capaian Ekonomi di Kecamatan Gu Kabupaten Buton Provinsi Sulawesi Tenggara - Taane La Ola, Iskandar; Mansyur, Akhmad (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2011)
This study aims to examine the role of social capital in economic development achievements in the Subdistrict of Gu, Buton District Southeast Sulawesi Province. The study uses trust and/or civic index method that is rated based on key answers of some basic questions. In addition, the regression equation is used to indicate the influence of trust and/or civic to the economic performance of the civil community in the villages. The result of this study shows that, first, moderate trust is dominated by social capital in the Gu Subdistrict, Buton District while very high trust has a small proportion of the community. Second, civic variables have a great influence on the economic achievement level. Although, civic variables has a small influence in comparison with trust variables. In conclusion, the main strength of the civil community in the Gu Subdistrict is at trust indicators.Civil Community, Trust, Civic, Economic Achievements